Análisis Presupuestario del Cuerpo de Bomberos de Puebloviejo - Valle Carrasco, Karen Estefania (2020)
All firefighting institutions carry out their budgetary proformas, which is the quantification of the income and expenses that have been projected for a certain period of time, so that they can start their activities according to said budget, which must be analyzed when closing of the accounting year, verifying that the proposed projection has been fulfilled, seeing the importance of this, the present case study topic was drafted which deals with: BUDGETARY ANALYSIS OF THE FIRE DEPARTMENT OF PUEBLOVIEJO. For the preparation of this case study, Information has been collected based on: The Fire Defense Law, COOTAD, Agreements and Resolutions concerning firefighting institutions, Public Procurement System, MEF, Regulation of Prevention and Mitigation and Protection Against Fire , INEC, Technical Budget Standards, Risk Management Secretariat. The application of this document originated according to the accounting information, found in the budget receipts of Income and Expenses for the period 2018, which was taken as a reference two indicators: sufficiency and effectiveness, to have a notion of the management of accounting management carried out the institution and thus be able to verify the level of compliance with Administrative Management.